Relationship between isotopic response (δ13C) and physicochemical properties: Taxonomy of soils in the Monzón Valley in the high jungle of Peru (Scientia Agropecuaria, 2025)
Identifying the carbon isotopic ratio is valuable for analyzing and understanding soil classification and dynamics. This study evaluated and related the soil isotopic ratio and its main properties (physicochemical) in the Monzón Valley. Fifteen pits were sampled within the strata of a toposequence. δ13C was determined using an isotope ratio mass spectrometry system coupled with an EA-IRMS elemental analyzer. To obtain accurate results, samples were categorized based on their depth. Between 500 and 600 µg of soil were weighed for samples
Keywords: C3 and C4 photosynthesis; soil profiles; agricultural crops